“Bachelor Girl Farmers” and the Queer Challenges to Western Heteronormativity - Korinek, Valerie (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2018)
Korinek’s article assesses the contribution of Imperial Plots to the writing of queer western histories, particularly women’s histories. The “single” English women who strike out for the west, individually and in pairs, challenge our preconceived notions of the presumed heterosexuality of all prairie settlers. Furthermore, Korinek argues that Carter’s research insights in this award-winning volume deserve to have a wide audience beyond the fields of gender histories, ideally integrated into scholarly and popular histories of the Canadian prairies and Canadian social histories.